Biocompatibility of ferroelectric lithium niobate and the influence of polarization charge on osteoblast proliferation and function. Issue 8 (25th December 2014) - Carville, N. Craig; Collins, Liam; Manzo, Michele; Gallo, Katia; Lukasz, Bart I.; McKayed, Katey K.; Simpson, Jeremy C.; Rodriguez, Brian J.
Abstract In this work, the influence of substrate surface charge on in vitro osteoblast cell proliferation on ferroelectric lithium niobate (LN) crystal surfaces is investigated. LN has a spontaneous polarization along the z‐axis and is thus characterized by positive and negative bound polarization charge at the +z and –z surfaces. Biocompatibility of LN was demonstrated via culturing and fluorescence imaging of MC3T3 osteoblast cells for up to 11 days. The cells showed enhanced proliferation rates and improved osteoblast function through mineral formation on the positively and negatively charged LN surfaces compared to electrostatically neutral x‐cut LN and a glass cover slip control. These results highlight the potential of LN as a template for investigating the role of charge on cellular processes. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2540–2548, 2015.